Adsorption kinetics and thermodynamics of yeast β-glucan for off-odor compounds in silver carp mince. (30th July 2020) - Zhang, Huimin; Wu, Dan; Huang, Qilin; Liu, Zhiyu; Luo, Xiaogang; Xiong, Shanbai; Yin, Tao
Highlights: YG had strong adsorption capacity for off-odor (hexanal, 1-octen-3-ol and nonanal). The adsorption process of YG for off-odor followed pseudo-first-order kinetic model. The adsorption was endothermic, spontaneous and driven by hydrophobic interaction. YG markedly reduced the contents of 3 off-odor compounds in silver carp mince. Abstract: Yeast β-glucan (YG) adsorbs off-odor in silver carp mince due to its more porous structure. To explore adsorption behavior and mechanism, adsorption kinetics and thermodynamics of YG for 3 off-odor compounds (hexanal, 1-octen-3-ol and nonanal) were investigated by pseudo-first/second-order models and isothermal equations (Langmuir, Freundlich and Redlich-Peterson). Kinetic experiments indicated adsorption process followed pseudo-first-order model. Adsorption isotherms indicated 3 off-odors could easily be adsorbed by YG and adsorption capacity was in the order of 1-octene-3-ol > hexanal > nonanal. Thermodynamic result suggested adsorption of 3 off-odors by YG was endothermic and spontaneous, and was driven predominantly by physisorption and hydrophobic interaction. Consequently, the contents of 3 off-odors that released from mince/YG complex decreased by 22.8%, 29.9%, and 24.5% ( p < 0.05), respectively, compared with those from mince without YG. Therefore, the addition of YG enhanced the binding capability to off-odors, thus reducing the release of off-odor from silver carp mince.